Oualitative, Quantitative Phytochemical Screening Of Musa Accuminata Barks Extract - Vadivel, S.A.; T.Sudha, T.Sudha (Journal of Neonatal Surgery, 2025)
Background: Medicinal plants have been widely explored for their bioactive compounds, contributing to their therapeutic potential. Musa acuminata (Musaceae family) is traditionally known for its pharmacological properties, but limited studies focus on the phytochemical composition of its bark extract. This study aims to perform qualitative and quantitative phytochemical screening of Musa acuminata bark extract to assess its bioactive constituents. Methods: The bark extract of Musa acuminata was obtained using by hydraulic pressure methods. Standard techniques were employed to conduct qualitative phytochemical screening to detect glycosides, alkaloids, flavonoids, phenolics, tannins, saponins, and terpenoids. The Folin-Ciocalteu method and the aluminum chloride method were utilized in order to carry out quantitative assessments of the total concentrations of phenolic compounds, flavonoids, tannins, and saponins, respectively. Results: According to the findings of the qualitative research, the plant contains a number of important phytochemicals, including alkaloids, flavonoids, tannins, and phenolics, all of which contribute to the plant's medicinal properties. With a 0.12 mg standard deviation, total alkaloid content was 4.25 mg GAE/g. The sample had 35.67 ± 0.85 mg GAE/g phenolic content, 18.34 ± 0.65 mg QE/g flavonoid content, 22.18 ± 0.48 mg GAE/g tannin content, and 6.75 ± 0.30 mg GAE/g saponin content. The sample has high bioactive chemical concentrations, according to the findings. Conclusion: The findings suggest that Musa acuminata bark extract is a rich source of bioactive phytochemicals, supporting its potential use in pharmaceutical and nutraceutical applications.